2007
DOI: 10.1177/1541204006297367
|View full text |Cite
|
Sign up to set email alerts
|

The Risk and Protective Factors of Violent Juvenile Offending

Abstract: Understanding the etiology of violent juvenile offending is critical for prevention and intervention efforts. The risk factors examined included marital status of parents, marital conflict, substance use, age of first substance use, learning difficulties, and school failure. The protective factors assessed included parenting styles, academic achievement, attitudes unfavorable toward violence, having a mentor, positive relationships with peers, and being involved in extracurricular activities. One hundred and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 22 publications
8
67
0
3
Order By: Relevance
“…Au-delà de ces divergences, l'abus de substances psychotropes est très prévalent chez les adolescents qui se suicident dans un contexte de détention. Dans une étude effectuée chez les adolescents incarcérés (Domalanta et al, 2003), 43 % des garçons et 36 % des fi lles avaient un problème d'abus d'alcool ; 27 % des garçons et des fi lles avaient un problème d'abus de substances psychotropes (Goldstein et al, 2005 ;Hart et al, 2007). En outre, l'abus de substances psychotropes et l'intoxication peuvent en soi exposer davantage les adolescents à des situations diffi ciles et ainsi interférer avec l'instauration de mécanismes d'adaptation effi caces, contribuant indirectement au risque suicidaire .…”
Section: Consommation De Substances Psychotropesunclassified
See 2 more Smart Citations
“…Au-delà de ces divergences, l'abus de substances psychotropes est très prévalent chez les adolescents qui se suicident dans un contexte de détention. Dans une étude effectuée chez les adolescents incarcérés (Domalanta et al, 2003), 43 % des garçons et 36 % des fi lles avaient un problème d'abus d'alcool ; 27 % des garçons et des fi lles avaient un problème d'abus de substances psychotropes (Goldstein et al, 2005 ;Hart et al, 2007). En outre, l'abus de substances psychotropes et l'intoxication peuvent en soi exposer davantage les adolescents à des situations diffi ciles et ainsi interférer avec l'instauration de mécanismes d'adaptation effi caces, contribuant indirectement au risque suicidaire .…”
Section: Consommation De Substances Psychotropesunclassified
“…Des lacunes ou un manque de confi ance dans ses habiletés de résolution de problèmes (American Academy of Child and Adolescent Psychiatry, 2001 ;Esposito et Clum, 2002 ;Speckens et Hawton, 2005), une moins bonne gestion de la colère et de la tristesse ainsi que la réaction aux événements diffi ciles en se blâmant ou en étant agressif seraient des facteurs de risque de suicide (Chagnon et al, 2001 ;Chagnon et al, 2007). Les adolescents délinquants de l'étude de Hart et al (2007) réagissaient plus souvent de façon agressive à la honte, témoignant possiblement de leur diffi culté à gérer les émotions négatives.…”
Section: Caractéristiques Individuelles Et De Personnalitéunclassified
See 1 more Smart Citation
“…On the other hand, some studies have found different risks for the development of behavior between men and women (Fagan, Van Horn, Hawkins, & Arthur, 2007;Gorman-Smith & Loeber, 2005;Hart, O'Toole, Price-Sharps, & Shaffer, 2007). For example, in a study by Fagan et al (2007) it was found that men, who had a greater number of peers with criminal behavior, were more rebellious and had academic failure and were more likely to commit criminal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Graham and Bowling used self-report data from a nationally representative random sample of 1721 young people in England and Wales and found that school truants usually had a poor relationship with one or both parents, family members in trouble with the law, low attachment to family and were poorly supervised in that their parents frequently did not know where their child was, whom they were with or what they were doing (Graham and Bowling, 1995 (Hart et al, 2007). Clearly parents have an important role to play in children's school adjustment, attendance and performance, however this is a complex association which is not necessarily unidirectional.…”
Section: Truancy Youth Anti-social Behaviour and Family Lifementioning
confidence: 99%